The development of social and emotional competence at school: An integrated model - Collie, Rebecca J. (International journal of behavioral development, 2020)
The aim of the current article is to extend prior conceptualizing by presenting a model of social and emotional competence that recognizes both the mechanisms and the manifestations of social and emotional competence. The Social and Emotional Competence School Model draws together conceptual underpinnings from the social and emotional competence literature along with theoretical grounding from self-determination theory and applies this within the schooling context. Social and emotional competence is operationalized by way of three components: basic psychological need satisfaction (of autonomy, competence, and relatedness), autonomous motivation, and behaviors. In the model, the three components form an iterative process of social and emotional competence development. Need satisfaction promotes social–emotional autonomous motivation and, in turn, socially and emotionally competent behaviors. The behaviors then promote need satisfaction in an ongoing cycle. The associations identified in the iterative process are impacted by need-support within the social environment, and the associations influence and are influenced by individual differences and human development.